Effect of e-beam sterilization on polypropylene/ethylene propylene diene monomer and ethylene vinyl acetate thermoplastic elastomer - Bellam Balaji, Anand (2018)
Thermoplastic elastomer is one of the priority polymeric compound identified for promotion and further development, given the growing demand for a number of commercial industries such as automobile, construction, footwear, healthcare, medical and food packaging sectors. In this study polypropylene (PP)/ethylene propylene diene monomer (EPDM) based thermoplastic elastomers are preferred for improving their properties as it can serve as a good replacement for PP or EPDM material, bridging the gap between thermoset and thermoplastic materials. This study focuses to develop PP/EPDM which can resist changes or improve properties when exposed to E-beam radiation, as E-beam also offers sustainable sterilization at low cost. The PP/EPDM blends with mixing ratios of 80/20, 50/50 and 20/80 were melt blended with the process parameters optimized using Design of experiments (DOE). The effect of E-beam on mechanical properties, thermal stability, crystallization and dynamic mechanical properties over the dose of 0 to 100 kGy were studied. The blends with high EPDM content (20PP/80EPDM) showed improvement in tensile strength up to 36% (at 40kGy and 60kGy) and resistant to impact strength up to 100 kGy, at the expense of elongation at break. On the other hand, the blends with high PP content (80 PP/20 EPDM and 50 PP/50 EPDM) showed detrimental effects on mechanical properties at all radiation dose studied and found to be not compatible for E-beam sterilization. Further, ethylene vinyl acetate (EVA) was incorporated to PP/EPDM blends at 10EVA/40EPDM/50PP, 20EVA/30 EPDM/50PP, 30EVA/20 EPDM/50PP and 40EVA/10 EPDM/50PP ratios. The gel content analysis showed that the efficiency of crosslinking decreased with increase in EVA loading. However, the presence of EVA in ternary blend especially facilitated the induction of sufficient crosslinks leading to improvement in tensile strength (up to 29% at 60 kGy), impact strength (up to 15% at 80 kGy) and retention of stiffness and thermal properties under radiation at the expense of elongation at break. In order to develop antibacterial ternary blends, silver nanoparticles (AgNP) were added by varying the loading from 0.3wt% to 1wt%. The Ag-ternary blends showed enhancement in impact properties (up to 9%) at the expense of decrement in tensile properties due to the agglomeration of AgNP. When, exposed to E-beam radiation, the mechanical and thermal properties exhibited similar trend of increment and decrement across radiation dose similar to the blends without AgNP. While, 1% Ag blend composites showed bacteriostatic effect on Staphylococcus aureuson, no significant reduction of Pseudomonas aeruginosa bacteria was observed. All the blends, before and after sterilization showed no significant toxicity on HaCaT cells investigated using in vitro analysis. Thus, the blends showed an instinct that their application could be extended to manufacturing of healthcare products and food packaging sector, as they are biocompatible and can withstand E-beam sterilization as demanded by the respective application. Among all the blends ternary blends studied (that exhibited biocompatibility even after radiation), 20EVA/30EPDM/50PP without AgNP showed the highest tensile strength of 18.41 MPa and impact strength of 43.64 J/m. Only a slight increase in tensile and impact properties was witnessed upon addition of 20% EVA to PP/EPDM blend in comparison to the binary blend (50PP/50EPDM blend). However, unlike the binary blend (whose properties decreased upon radiation), the ternary blend (20EVA/30EPDM/50PP) showed improvement in tensile strength up to 29% at 60kGy and up to 15% increase in impact strength at 80kGy.